Exploring the Role and Mechanism of Imatinib in Chronic Unpredictable Mild Stress-induced Depression Model of Rats - Wang, Xiaohui; Li, Yajing; Shen, Yinxue; Zhang, Dongzi (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: The study was planned to examine the potential effect of imatinib in chronic unpredictable mild stress (CUMS)-induced depression model of rats. Materials and Methods: Male rats were subjected to the 6-week CUMS with unpredictable stressors to induce depression and the imatinib was started from the 4th week (for 21 days during 6 weeks of the protocol). Results: CUMS significantly increased immobility time and decreased consumption of sucrose in the swimming and sucrose preference test respectively. Furthermore, a considerable reduction in the Brain-derived neurotrophic factor (BDNF) levels and an increase in phosphorylated NF-kB levels (p-NF-kB) were noticed in the prefrontal cortex (PFC). However, imatinib (25 and 50 mg/kg) significantly reversed sucrose consumption as well as reduced immobility times in CUMS-subjected rats, suggesting the antidepressant potential of imatinib. Moreover, imatinib treatment significantly increases in the levels of BDNF and a decrease in the p-NF-kB levels in the PFC of the brain of stress-subjected rats. The co-administration of tropomyosin receptor kinase B (TrkB) antagonist, ANA-12 (0.25 and 0.5 mg/kg) with imatinib (50 mg/kg) considerably attenuated imatinib-mediated antidepressant effects in sucrose preference behavior and immobility period in CUMS subjected rats. ANA-12 abolished imatinibinduced effects in stress-subjected rats. Conclusion: The antidepressant actions of imatinib may be attributed to an increase in the BDNF levels and a decrease in the p-NFkB levels in the stress-susceptible PFC region of the CUMS subjected rats.
Keywords: CUMS; Depression; p-NF-kB; BDNF; Imatinib